Expression and Clinical Correlation Analysis Between Repulsive Guidance Molecule a and Neuromyelitis Optica Spectrum Disorders - Tang, Jinhua; Zeng, Xiaopeng; Yang, Jun; Zhang, Lei; Li, Hang; Chen, Rui; Tang, Shi; Luo, Yetao; Qin, Xinyue; Feng, Jinzhou (Frontiers in Immunology, 2022)
Objectives: This study aims to explore the expression of Repulsive Guidance Molecule a (RGMa) in neuromyelitis optica spectrum disorders (NMOSD) and to explore the correlation between RGMa and the clinical features of NMOSD. Methods: 54 NMOSD patients and 22 age-matched healthy control (HC) patients were enrolled from October 2017 to January 2020. Patients’ demography and clinical features including Expanded Disability Status Scale (EDSS) score, degree of MRI enhancement, and AQP4 titer were collected. Patients were then sub-classified into 4 groups（acute phase/reemission group,AQP4+/AQP4- group） based on their clinical characteristics. The expression of serum RGMa was measured by enzyme linked immune-assay (ELISA) and compared across 4 patient groups. Correlation between RGMa serum expression level and individual clinical feature was explored using Pearson and Spearman correlation analysis. Results: 54 cases of NMOSD patients were composed of 14 males and 41 females. The serum expression of RGMa in the NMOSD group was significantly higher than the HC group (p < 0.001). Among the patient group the acute phase group and the AQP4 positive group exhibited significant higher serum RGMa level comparing to the remission group (p < 0.001) and the AQP4 negative group (p < 0.05) respectively. A significant positive correlation was observed between RGMa expression in NMOSD with EDSS score, degree of MRI enhancement, segmental length of spinal cord lesions and AQP4 titer(p<0.001) while a significant negative correlation was observed with delta EDSS score (p < 0.001). Conclusions: Current study suggested that RGMa may be considered as a potential biomarker for predicting the severity and clinical features of NMOSD. The involvement of RGMa in the pathogenesis of NMOSD remains to be explored.